How do you multiply 5mn(7m-2n)5mn(7m2n)?

1 Answer
Mar 13, 2018

See a solution process below:

Explanation:

Multiply each term within the parenthesis by the term outside the parenthesis. Use these rules for exponents:

a = a^color(red)(1)a=a1 and x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))xa×xb=xa+b

color(red)(5mn)(7m - 2n) =>5mn(7m2n)

(color(red)(5mn) xx 7m) - (color(red)(5mn) xx 2n) =>(5mn×7m)(5mn×2n)

(color(red)(5m^1n) xx 7m^1) - (color(red)(5mn^1) xx 2n^1) =>(5m1n×7m1)(5mn1×2n1)

35m^(1+1)n - 10mn^(1+ 1) =>35m1+1n10mn1+1

35m^2n - 10mn^235m2n10mn2